Modelling of coastal hydrodymics associated with coastal structures: A review - Hashim, R. (2013)
Coastal hydrodynamics related to wave, current and wave-current interactions are important for many coastal engineering design and application. They allow the study of new engineering methods for coastal defense and play an essential role in the calculation of sediment transport and morphological evolution. Prediction of hydrodynarnic associated with coastal structures has been largely relied on the empirical relation in the last 28 years supported by physical tests. Due to recent advances in the computer power and development experienced by numerical models, use of a number of coastal hydrodynarnic modeling has become a promising alternative to predict coastal hydrodynarnic and the most feasible approach to solve the hydrodynarnic problems. However, the simulation results produced by these models depends on model concepts used; consideration of hydrodynarnic processes such as wind shear, wave forces, wave transformation (breaking, shoaling, roller effect, diffraction, transmission), tidal forces; and scales of the application. Effective modeling of the coastal hydrodynarnic allows the identification of the best protection techniques for a certain coastal area. Then, a proper understanding of the model concepts is necessary to achieve an optimal functional design. This paper attempts to review available hydrodynarnic models and discuss the characteristic of those models generally.